O lugar do trabalho reprodutivo: um estudo com donas de casa da cidade de Fortaleza - Meyer, Antônia Vaneska Timbó de Lima (2018)
The present study aimed to understand the place of reproductive work for housewives in the city of Fortaleza - CE. We understand that women have always been inserted in the working world, initially in the domestic sphere and in parental care, which is gradually being recognized through new regulations as work. After the Industrial Revolution, this feminine performance becomes more representative compare to the mass of workers, and remains increasing in contemporaneity. However, their participation in the working world has always been markedly precarious (partial days, subcontracts, temporary jobs, outsourcing, for instance). In addition to this, women still have a large part of domestic work and parental care, as studies on the Sexual Division of Labor point out. However, there is a contingent of women who remain exclusively in the domestic sphere, hereinafter referred to as housewives, and who exclusively deal with reproductive, invisible and unpaid work. Anchored in this reality, we take as research subjects the housewives of the city of Fortaleza - CE, in order to understand the work reality of these women, who are often “socioeconomically invisible”. The methodology of the research was qualitative, in which were used for data collection the field diary and individual semi-structured interview, which were recorded and transcribed. The analysis of the data was done through the Thematic Analysis, situated within the Content Analysis. We take the theories of the Sexual Division of Labor, within the framework of social sex relations, and the Social Times Theory, besides the optics of the Social Psychology of Work, as theoretical and analytical contributions that supported the analysis of the material erected in the study. As results, we have obtained that the work of the housewives researched occupies the place of centrality in their lives, exerting a structuring and organizing character of the daily life of these women, who see themselves as legally unrecognized workers.